2014
DOI: 10.7567/jjap.53.05fb23
|View full text |Cite
|
Sign up to set email alerts
|

Water adsorption and desorption on plasma-activated PET film surface, indication of hydrogen bonding

Abstract: A plasma-irradiated poly(ethylene terephthalate) (PET) film has a long lifetime of bonding capability. To clarify its origin, a PET film was irradiated with oxygen plasma. It was then exposed to normal atmosphere including water vapor. FTIR absorption on the irradiated and non-irradiated films was measured at different times after the start of evacuation. The irradiated film has a larger amount of OH than the non irradiated film, and OH is generated on the film surface. The irradiated film has a larger amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…This finding indicated that carboxylic acid (COOH) groups were formed on the polyester fabric , after the EWNS treatment. The COOH group is a polar functional group that is created by the reaction between OH • and polyester through cross-linking and functionalizing with and without chain scission. The increase in the number of polar groups can increase the surface energy of a fabric and improve its wettability. ,,, Therefore, the improvement in the wetting ability of the EWNS-treated sample could be attributed to the increase in the number of COOH groups on the fabric, leading to an increased fabric surface energy and enhanced wetting behavior. Certain other changes were noted in the different band regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicated that carboxylic acid (COOH) groups were formed on the polyester fabric , after the EWNS treatment. The COOH group is a polar functional group that is created by the reaction between OH • and polyester through cross-linking and functionalizing with and without chain scission. The increase in the number of polar groups can increase the surface energy of a fabric and improve its wettability. ,,, Therefore, the improvement in the wetting ability of the EWNS-treated sample could be attributed to the increase in the number of COOH groups on the fabric, leading to an increased fabric surface energy and enhanced wetting behavior. Certain other changes were noted in the different band regions.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, these species can destruct the microbial cell envelope by fragmenting certain proteins. , Therefore, the EWNS technology has the potential to improve the antibacterial properties of textile materials. In addition, the OH • in the EWNSs is highly active and can easily react with certain textile materials, thereby forming polar functional groups on the surface of the materials. In this manner, the wettability of certain textiles can be enhanced. Moreover, because the ROS can lead to protein denaturation and lipid peroxidation reactions, , the ROS contained in the EWNSs can roughen the surface of certain protein fibers, thereby changing the friction-related properties such as antipilling properties.…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to the formation of dipoles on the surface of the dielectric, with a positive polarity outward and negative polarity inward that attracts polarized molecules such as water [27]. The contact angle behavior is similar to that of plasma-activated polyethylene terephthalate, where it is attributed to the formation of active OH surface groups, possibly indicating hydrogen bonding with water [29]. Also, the presence of water soluble impurities like salts or hygroscopic dust on uncleaned surfaces may cause formation of conductive aqueous layers at the deliquescence humidity which may lie below RH of ∼60% [9].…”
Section: Dielectric Damagementioning
confidence: 90%